2013
DOI: 10.1021/nl400924c
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Vertical GaAs Nanowires on an Amorphous Substrate via a Fiber-Textured Si Platform

Abstract: We demonstrate the vertical self-catalyzed molecular beam epitaxy (MBE) growth of GaAs nanowires on an amorphous SiO2 substrate by using a smooth [111] fiber-textured silicon thin film with very large grains, fabricated by aluminum-induced crystallization. This generic platform paves the way to the use of inexpensive substrates for the fabrication of dense ensembles of vertically standing nanowires (NWs) with promising perspectives for the integration of NWs in devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…The cation exchange reaction is driven by a large excess of the incoming cation and/or the preferential solvation of the outgo- [37]. These authors used a gold particle as a catalyst to grow a semiconducting nanowire using the appropriate gaseous reactant, Figure 1a While CVD is a clean method well suited to the growth of semiconductor core/shell materials [37,39], different methods have to be developed for other systems such as metals. Habas et al have shown that metal nanocrystals can be used as seeds for growing a metal crystalline shell [40].…”
Section: Cation Exchangementioning
confidence: 99%
“…The cation exchange reaction is driven by a large excess of the incoming cation and/or the preferential solvation of the outgo- [37]. These authors used a gold particle as a catalyst to grow a semiconducting nanowire using the appropriate gaseous reactant, Figure 1a While CVD is a clean method well suited to the growth of semiconductor core/shell materials [37,39], different methods have to be developed for other systems such as metals. Habas et al have shown that metal nanocrystals can be used as seeds for growing a metal crystalline shell [40].…”
Section: Cation Exchangementioning
confidence: 99%
“…[1][2][3] Besides, orientationcontrolled poly-Si layers are essential for fabricating antireflective structures, controlled nanostructures, and tandem structures with advanced materials. [4][5][6] Al-induced crystallization (AIC) has gained much attention as a way to form poly-Si on glass below the softening temperature of glass (550 C). In this technique, an amorphous Si (a-Si) layer on Al is crystallized by exchanges between the Al and Si layers during annealing (425-500 C).…”
Section: Introductionmentioning
confidence: 99%
“…NW solar cells on cheap substrates: Unlike thin-film structures, NW growth has much wider choices in the substrate selection, which benefits from its good strain accommodation ability mentioned above. The integration between large lattice mis-matched material systems have been reported, such as InP/Si (8.1%) and InAs/Si (11.6%) [174][175][176][177][178]. Besides the single crystalline and polycrystalline substrates, the NWs can also be grown on graphene, carbon nanotube, fibre-textured silicon thin film, amorphous Si, glass, and indium tin oxide [179][180][181][182][183][184].…”
Section: Design For Novel High-efficiency and Low-cost Solar Cellsmentioning
confidence: 99%